Evaluation of the antibacterial synergism of two plant extracts belonging to Bignoniaceae family and development of a topical formulation - Torres, Carola Analía (2022)
Fridericia caudigera and Cuspidaria convoluta (Bignoniaceae) species, which grow in the northwest of Argentina, have shown antibacterial effect against strains isolated from skin infections, and each one displayed synergism with commercial antibiotics. The aims of this work were to evaluate the antibacterial activity and toxicity of the combination of these two plant species, and to design a stable gel for topical use including the blend of extracts. The combination of extracts was evaluated for synergistic effects (chequerboard assay), genotoxicity (Ames test) and cytotoxicity (Artemia salina test). A gel was subsequently formulated with the combination of extracts using carboxymethylcellulose as a polymer. The following physicochemical characteristics of the gel formulation: pH, viscosity, spreadability and total phenol content, as well as resistance to severe temperature changes, biological activity (diffusion in agar), in vitro permeation (Franz cells) and primary dermal irritation (Draize test) were analyzed. The combination of extracts showed a synergistic effect on pathogenic bacteria and was not toxic in the in vitro tests. The gel was stable and retained the antimicrobial activity of the original extracts. The formulation proposed in this work could constitute an alternative for primary skin infections since it proved to be safe for topical administration.